Different perspective on teaching socio-scientific subjects - Erol Koçoğlu; Özlem Ulu Kalin; Fatıma Betül Demir (Intelektual Pustaka Media Utama, 2022)
In the ever-changing world based on the needs, curiosity and entrepreneurial drive of the humankind, interest in socio-scientific issues has been increasing every day with the discussion and different approaches in society. It could be suggested that the increase in this interest has been due to both the contribution and damages of these issues to the environment. The present study aimed to analyze the socio-scientific issues instructed with various strategies, methods and techniques in different learning environments in educational institutions as a result of the developments in science and technology due to social needs based on teacher perceptions. The study group included 50 teachers in different fields and employed in various schools in Turkey. The study sample was assigned with criterion sampling technique and the admission criterion was employment in Turkish public schools. In the study, the data were collected with a semi-structured interview form developed by the authors, and the findings were analyzed with content analysis. The study findings demonstrated that the teachers in the study group had different and significant perceptions on the instruction of socio-scientific topics in learning environments.